Silsesquioxane-modified chitosan nanocomposite as a nanoadsorbent for the wastewater treatment - AYDIN URUCU, OYA (ELSEVIER SCIENCE BV, 2019)
In this study, synthesized polyhedral oligomeric silsesquioxanes (POSS with eight arms of di(ethylene glycol) oxides)) and chitosan based nanocomposite materials (PSCS-(1,2,3)) were prepared by varying the cross-linker ratio while keeping POSS and chitosan quantities constant. Among the prepared nanocomposites, PSCS-2 was found to be the most effective nanoadsorbent for the treatment of wastewater containing cadmium (Cd (II)) because of having a balance between the availability of functional sites and the stability of the nanocomposites. The influence of pH, saturation time, initial metal concentration was determined under the optimum conditions. The adsorption property of the nanocomposite material was investigated by the Langmuir and Freundlich adsorption isotherms. The Langmuir isotherm well fitted for metal ion adsorption on PSCS-2. This result was attributed to the succeeding of the smooth surface morphology thanks to the good solubility and dispersibility of the POSS molecules in the organic chitosan environments. Therefore, the use of POSS reinforced chitosan nanocomposite to treat heavy metal pollutants in wastewater is promising and deserves further investigation.
Keywords: Polyhedral oligomeric silsesquioxanes (POSS); POSS/chitosan based nanocomposite; Sol-gel method; AAS; Cadmium (II); Adsorption; FUEL-CELL; REMOVAL; MEMBRANES; POSS; CHITIN; PERFORMANCE; DENDRIMERS; POLYMERS; BEHAVIOR; CADMIUM